Correlation between nitrite accumulation and the concentration of AOB in a nitritation reactor - Im, Jiyeol; Jung, Jinyoung; Bae, Hyokwan; Kim, Daeik; Gil, Kyungik (SPRINGER, 2014)
Nitritation is an innovative biological nitrogen removal method in wastewater, and it has the advantages of energy and economy. The correlation between a nitrite conversion rate and the gene copy numbers of ammonia oxidizing bacteria (AOB) in a nitritation reactor was examined to measure the effectiveness of removing a nitrogen content in a biological nitrogen removal process, using a biological process of nitritation. A laboratory scale reactor was prepared and operated for over a year, using digester supernatant to induce a stable nitritation, and to optimize the operational conditions by adjusting various operating factors. The relationship between operational results of nitritation reactor and the AOB gene copies was approximated through identification and quantitative analysis of AOB. A stable nitritation can be artificially led with the control of SRT, while treating anaerobic digester supernatant from MWTPs. And AOB gene copies showed a correlation with free ammonia (FA) inhibition and performance of nitritation, and AOB activity. Thus, AOB gene copies were found important when it comes to analyzing nitritation.
Keywords: WASTE-WATER; AMMONIA; NITRIFICATION; INHIBITION